China in Innovative Development of Alternative Energy Advanced Industrial Technologies - Dudin, Mihail Nikolaevich; Frolova, Ð•vgenia Ð•vgenevna; Kucherenko, Petr Aleksandrovich; Vernikov, Vitaly Aleksandrovic; Voykova, Natalia Andreevna (International Journal of Energy Economics and Policy, 2016)
The purpose of this article is to study the specifics of renewable energy development in China, including solar, as well as to identify the main factors limiting the ubiquity of solar energy in the country. Among the main objectives of the article, it makes sense to highlight the following: a study of historical preconditions for the formation of the renewable energy segment in the national energy sectors; an analysis of the main trends in socio-economic and energy development in China; an evaluation of China’s activity in the exploitation of renewable energy sources; consideration of the most important prospects and limitations in the use of solar energy. Keywords: Renewable Energy; Solar Energy; China; Conventional Energy Production; Photovoltaic Cells; Electric Power JEL Classifications: Q42, Q48, O31